Structural and Functional Approach to Study of Psychological Loneliness - Lyubyakin, A (KnE Life Sciences, 2018)
The article discusses the possibility of studying the psychological aspects of loneliness in the context of problems of personality adaptation and the risks of adaptive chokes. Loneliness is the result of a low level of adaptation or the result of disadaptation processes. Personality is considered functionally as a means of adaptation primarily to the social environment. The basic components of the personality structure are also considered functionally as tools for adaptation. The socio-psychological version of the personality structure is taken as the basis, which includes social roles, selfconcept, and personality orientation in their interrelationship. The experience of loneliness is associated with adaptive dysfunctions of individual components of the personality. The risks that are carried by a social role as a possible factor in the complication of relations or the emergence of acute conflicts with surrounding people and personalities themselves and, as a consequence, the experience of a feeling of loneliness, are considered. Dysfunctions of the self-concept are associated with crises or identity deformation, self-esteem deformation, contradictions, the discrepancy between external, public self, and inner self. Orientation as the main vector of personality activity is considered as an important factor of adaptation, harmonization of relationships with the social world. Difficulties in this area, difficulties in working out a life programme, its correction, or radical changes under the influence of life experience also carry risks of disadaptation and psychological loneliness. For a certain period of time, the purposeful activity of the individual can be blocked, which is a serious psychological problem and a destructive factor of social alienation and self-alienation. Dysfunctions of one of the components of the personality structure will not create radical problems if they are not observed in other components of the personality structure. The greatest risks of social isolation and loneliness are associated with the destabilisation of the structure of the individual as a whole. This leads to a full-scale disorder of the person with the surrounding world and himself/herself, which guarantees disadaptation and intense experiences of loneliness. Keywords: psychological loneliness, adaptation and disadaptation of personality, socio-psychological structure of personality, social roles, self-concept, personality orientation, dysfunctions in personality structure.